The role of anatomical variations in osteomeatal unit in the aetiology of chronic rhinosinusitis - Azila, Alias (2008)
The complexities of the nose and paranasal sinuses anatomy, as well as their multiple functions make the sinuses an interesting and rewarding topic of study especially at the region of osteomeatal complex (OMC). Congenital anomaly in this region, though rare, may create technical difficulties during surgery. However, the role of anatomical variations in pathogenesis of sinusitis is still unclear. OBJECTIVE The aims of the study was to look into the anatomical variations in the osteomeatal complex in chronic rhinosinusitis patients, to determine the association between bony anatomical variations in osteomeatal complex with chronic rhinosinusitis (CRS) and to determine· the main anatomical variations in the osteomeatal complex which are usually depicted by computed tomography (CT) and nasoendoscopy in patients with CRS and normal patients without CRS. METHODOLOGY A case control study was done in which we had reviewed the CT scan of paranasal sinuses (HRCT) images of 240 individuals, 120 cases of CRS and another 120 patients without CRS problem. Their paranasal sinuses CT scan obtained 1.25mm thicknesses in axial and coronal planes with high resolution technique were reviewed. The data were analysed using Pearson ·chi Square test. RESULT The anatomical variations recorded were: Concha bullosa in 49 cases (40.8%) among the CRS and 57 cases (47.5%) among patients without CRS, Paradoxical middle turbinate in 14 cases (12.0%) of CRS and 27 (23.0%) in patients without CRS, pneumatized uncinate process were found in 3 cases (3.3%) of CRS cases while in patients without CRS 3 cases (3.3%) as well, Haller's cells (infraorbital ethmoid cell) in 61 (51.0%) cases of CRS while 75 cases (62.0%) cases of patients without CRS, pneumatized agger nasai cell 100 (83.0%) in CRS and 95 (79.0%) in patients without CRS, deviated nasal septum in 67 cases (56.0%) of CRS while in patients without CRS 73 (60.8%) cases and "lastly pneumatized septum seen in 4 (3.3%) cases of CRS and none in patients without CRS. However 'the presence of single anatomical variation itself does not have significant association with the genesis of CRS except for paradoxical middle turbinate and infraorbital ethmoid cell. CONCLUSION The most common anatomical variation in osteomeatal complex in CRS patients are pneumatized agger nasi cell , followed by baUer's cell, DNS, right concha bullosa, left concha bullosa, paradoxical middle turbinate, pneumatize uncinate proces~ and lastly septum pneumatization. And the single ~ccurence of an anatomical variant itself does not establish the genesis of the CRS disease except for paradoxical middle turbinate and infraorbital ethmoid cell.